Do small group health insurance regulations influence small business size? - Kanika Kapur; Pinar Karaca-Mandic; Susan M. Gates; Brent Fulton (University College Dublin, UCD School of Economics, 2006)
The cost of health insurance has been the primary concern of small business owners for several decades. State small group health insurance reforms, implemented in the 1990s, aimed to control the variability of health insurance premiums and to improve access to health insurance. Small group reforms only affected firms within a specific size range, and the definition of the upper size threshold for small firms varied by state and over time. As a result, small group reforms may have affected the size of small firms around the legislative threshold and may also have affected the propensity of small firms to offer health insurance. Previous research has examined the second issue, finding little to no effect of health insurance reforms on the propensity of small firms to offer health insurance. In this paper, we examine the relationship between small group reform and firm size. We use data from a nationally representative repeated cross-section survey of employers and data on state small group health insurance reform. Contrary to the intent of the reform, we find evidence that small firms just below the regulatory threshold that were offering health insurance grew in order to bypass reforms.
hdl:10197/291
Keywords: I18; L25; 330; Health insurance; small business